Ingresos y su incidencia en la rentabilidad de la Empresa Comercial El Especialista del Agro S.A. del cantón San Juan durante la pandemia - Cedeño Uca, Marcos Adrian (2020)
In the present case study that is called with the name of, Income and its incidence in the profitability of the commercial company, the Specialist of Agro S.A of the San Juan canton during the pandemic. Its investigative justification is to examine the process of operating expenses during the COVID-19 pandemic, establishing the accounting processes and techniques that influence the profitability or financial management, tax and social commitment of the company's employees. Its systematization and research process is contains simple descriptive foundations because it allows to make ideas to explicitly reveal the controversy and the difference on the subject organizes the usual procedure of the scientist to obtain answers to his questions or to verify the research hypotheses. To achieve the staff model of workers of the commercial company El Especialista del Agro S.A, the learning process was carried out together with the team of work personnel, events, communities, etc. The consequences of the application of review and strategy are in order to obtain a greater benefit and optimal profitability in the commercial company the Agro Specialist SA, At the end of the financial process of 2020, it is intended to improve at the level of profitability and management to workers, customers, suppliers, etc.